PROGRAM DANA DESA DAN PEMBERDAYAAN MASYARAKAT DI DESA SRIKATON - Dr. Hajar G Pramudyasmono (Jurnal Sosiologi Nusantara, 2020)
This research was conducted in Srikaton Village, Pondok Kelapa Sub-District, Central Bengkulu District. The aim is to confirm the amount of village funds allocated by the central government to this village in 2019. Then, this research also explores information about the proportion of village funds used for community empowerment. The informants of this study were selected based on purposive sampling technique. They are two village officials taking care of and knowing about the use of village funds. The data were collected by using observation, interview, and documentation methods. The collected data were then analyzed and presented using quantitative descriptive methods in the form of percentage analysis. This research notes that the village funds in Srikaton in 2019 were used to finance the construction of physical infrastructure (70%), while another 30% was used to finance community empowerment programs, such as training on entrepreneurship. The village funds were not used to grant business financial for poor families. As a result, the village fund program in Srikaton does not directly reduce poverty.Keywords: village funds, empowerment, poor families.